Railway Infrastructure Financing and Charging System in Poland - Pieriegud, Jana (Univerzita Pardubice, 2008)
There are various problems regarding the financing of transport infrastructure in Poland, like in any other country, which is planning and relizing infrastructure funding, which have been introduced in 2006, created frameworks for increasing expendituresfor the maintance and development of railway infrastructure. The key role in this process to the state guarantees ensuring the continuity of transferring declared budget funds. The paper includes an analysis of railway infrastructure investment needs as well as the volume and structure of outlays in Poland 2003-2008. Moreover, the main issues connected with calculating access charges are being presented. In the conclusion the barriers in the proces of railway infrastructure maintenance and development are summed up.